Supervisory Role of The Financial Services Authority in Utilizing Equity Crowdfunding in Indonesia - Irawati Irawati (LAW REFORM, 2020)
In order to provide legal certainty and protection for those involved in investment in Indonesia, the Financial Services Authority has officially issued regulations relating to the collection of funds through information technology-based stock offers or equity crowdfunding. This article aims to review the role of supervision by the Financial Services Authority and the form of mitigation risks to obstacles and problems in utilizing Equity Crowdfunding in Indonesia. The research method used is normative juridical with, using secondary data which is then analyzed qualitatively. The results showed that the Financial Services Authority in conducting supervision of the use of Equity Crowdfunding can be done off site, or On Site. Risk mitigation must be carried out by the Financial Services Authority both through regulations and concrete steps. In the implementation of risk mitigation, the Financial Services Authority can also involve the Indonesian Fintech Association to address risks in order to provide a sense of security for investors and publishers in the use of the Equity Crowdfunding platform in Indonesia.